Determinant Factors Of Consumer Demand For Cooking Oil In Indralaya Indah District Indralaya District Ogan Ilir Regency: Faktor Determinan Permintaan Konsumen Minyak Goreng Di Kelurahan Indralaya Indah Kecamatan Indralaya Kabupaten Ogan Ilir - Hutabarat, Indri Marsella; Purbiyanti, Erni; Sulastri, Merna Ayu (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
Cooking oil is one of the basic ingredients which plays a very important role in meeting household consumption needs. Currently, cooking oil is marketed in two forms, namely in bulk and in packages with certain brands/labels. Even though packaged cooking oil has many advantages and is increasingly common in Indralaya Indah Village, the demand for bulk cooking oil is still higher compared to packaged cooking oil. The objectives of this research are: (1) to analyze the differences in the characteristics of packaged cooking oil and bulk cooking oil in Indralaya Indah Village, Ogan Ilir Regency; (2) to analyze the determinant factors for packaged cooking oil and bulk cooking oil in Indralaya Indah Village, Ogan Ilir Regency (3) to describe the behavior of using and handling packaged cooking oil waste by households in Indralaya Indah Village, Ogan Ilir Regency. This research was carried out in December in Indralaya Indah Village, Indralaya District, Ogan Ilir Regency. The research method used was a survey with a sample of 38 households. Data were processed using multiple linear regression analysis, independent t test and descriptive analysis. The results of this research show that: (1) the characteristics of cooking oil consumers obtained from this research, namely consumers aged 36-45 years, the dominant gender is female, the education level is predominantly high school level, and have a relatively high income of between Rp. 2,500,000 – 3,500,000, and have < 4 family members. Meanwhile, the significant differences in the characteristics of bulk cooking oil and packaged cooking oil are education, number of family members and employment; (2) factors that influence consumer demand for cooking oil per month in Indralaya Indah Subdistrict are education, income and health awareness; (3) the behavior of using cooking oil in Indralaya Indah Subdistrict, Ogan Ilir Regency, namely that on average, 358 milliliters of cooking oil is used for one cooking and it is immediately thrown into the drain of each respondent's house without processing it first. Keywords: behavior, characteristics, cooking oil, disposal, factors, waste